and are positive integers such that and the expression below is an integer: Find the sum of all values of less than that satisfy the above conditions.
Inspiration: [Problem #1, Spain Mathematical Olympiad, 1996]
and are positive integers such that is an integer. Show that the greatest common divisor of and is not greater than .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Vieta Root Jumping
We use Vieta jumping method for solving this problem. Write b a + 1 + a b + 1 = k ⟹ a 2 + a + b 2 + b = k a b ⟹ a 2 + ( 1 − k b ) a + b 2 + b = 0 , where k is a positive integer and last equation is a quadratic in terms of a . Suppose that ( a 0 , b 0 ) is a solution to the above quadratic, with a 0 ≥ b 0 . If we let b = b 0 , equation has two solutions: a = a 0 and a = a ∗ . By Vieta's formulas a 0 + a ∗ = k b 0 − 1 and a 0 a ∗ = b 0 2 + b 0 . Observe that a ∗ = k b 0 − 1 − a 0 is an integer, and a ∗ = a 0 b 0 2 + b 0 is positive.
Therewith, if a 0 ≥ b 0 b 0 2 + b 0 = b 0 + 1 , then a ∗ = a 0 b 0 2 + b 0 ≤ b 0 , and we can choose ( a 1 , b 1 ) = ( b 0 , a ∗ ) as a solution to the equation. Note that a 1 + b 1 = b 0 + a ∗ < a 0 + b 0 . In a similar manner, we can construct an another solution ( a 2 , b 2 ) such that a 2 + b 2 < a 1 + b 1 and etc.
Well-ordering principle tells us that we cannot repeat this procedure ( Fall! ) forever! Therefore, we will encounter a solution ( a n , b n ) where a n < b n b n 2 + b n = b n + 1 , and we can no longer jump downwards. Now we must find the possible values of ( a n , b n ) , i.e., possible values of the smallest solution. Note that b n ≤ a n < b n + 1 . It follows that a n = b n , put this back in the original equation: a n 2 + ( 1 − k a n ) a n + a n 2 + a n = 0 ⟹ a n + 1 − k a n + a n + 1 = 0 ⟹ k = a n 2 ( a n + 1 ) Therefore a n ∣ 2 ( a n + 1 ) or a n ∣ 2 ( a n + 1 ) − 2 a n = 2 , which gives a n = 1 , 2 with k = 4 , 3 , respectively. So we must reconstruct solutions ( Rise! ) using two cases: ( a n , b n ) = ( 1 , 1 ) with k = 4 and ( a n , b n ) = ( 2 , 2 ) with k = 3 .
Notice that ( a n , b n ) = ( b n − 1 , k b n − 1 − a n − 1 − 1 ) and since a n = b n − 1 we get ( a n − 1 , b n − 1 ) = ( k a n − b n − 1 , a n ) .
Above recurrence relation gives the values of a less than 1 0 0 0 , for ( a n , b n ) = ( 1 , 1 ) with k = 4 , as ( 1 , 1 ) , ( 2 , 1 ) , ( 6 , 2 ) , ( 2 1 , 6 ) , ( 7 7 , 2 1 ) , ( 2 8 6 , 7 7 ) . And gives the values of a less than 1 0 0 0 , for ( a n , b n ) = ( 2 , 2 ) with k = 3 , as ( 2 , 2 ) , ( 3 , 2 ) , ( 6 , 3 ) , ( 1 4 , 6 ) , ( 3 5 , 1 4 ) , ( 9 0 , 3 5 ) , ( 2 3 4 , 9 0 ) , ( 6 1 1 , 2 3 4 ) . Thus the answer is 1 + 2 + 3 + 6 + 1 4 + 2 1 + 3 5 + 7 7 + 9 0 + 2 3 4 + 2 8 6 + 6 1 1 = 1 3 8 0 .